National Velvet [videorecording (DVD)] - Brown, Clarence, 1890-1987; Rooney, Mickey; Crisp, Donald, 1880-1974; Taylor, Elizabeth, 1932-2011; Revere, Anne, 1903-1990; Lansbury, Angela, 1925-; Treacher, Arthur, 1894-1975; Owen, Reginald, 1887-1972; Kilburn, Terence; Bagnold, Enid (Warner Home Video : Turner Entertainment Co., 2000)
A jaded former jockey helps a young girl prepare a wild but gifted horse for England's Grand National Sweepstakes.